FUTSAL : THE INDOOR GAME THAT IS REVOLUTIONIZING WORLD SOCCER - Fahey, Jamie (Melville House Publishing, 2021)
"The untold story of soccer's little brother futsal, the grassroots game that is the secret behind the success of Pelé, Neymar, Messi, Ronaldo and the US star Christian Pulisic Futsal, a form of indoor soccer, is one of the fastest growing sports in the world. Jamie Fahey uncovers its global stories, tactical innovations and fascinating history and reveals its the secret behind the success of the likes of Brazilians Ronaldhino, Ronaldo Fenômeno and Romario and the kind of soccer revolutionized by Pep Guardiola at Barcelona--with Spain's Xavi Hernández and Andrés Iniesta--and at Manchester City, with Belgium's Kevin De Bruyne and Brazilian goalkeeper Ederson. Born in Uruguay almost a century ago but raised to an art form in Brazil, futsal is one of the fastest-growing sports on the planet: over 60 million people play this lightning-fast and tactically intricate variation of indoor soccer, which is also a bona fide professional sport in its own right. Despite its growing status, however, futsal's history remains largely unknown and untold"--